Atherosclerosis Burden in Patients with Acute Chest Pain: Obesity Paradox. (12th January 2014) - Chaikriangkrai, Kongkiat; Kassi, Mahwash; Khaleel bala, Sayf; Nabi, Faisal; Chang, Su Min
Abstract : Obesity paradox has been described in various populations of coronary artery disease, mainly asymptomatic subjects. However, relationship between obesity and coronary artery calcification detected by cardiac CT in symptomatic patients has rarely been demonstrated. This study seeks to investigate whether the paradoxical relationship between obesity and coronary artery calcification exists in patients with acute chest pain. A final cohort of 1030 chest pain patients presenting at our emergency department who underwent coronary evaluation by multidetector cardiac CT were examined. With absent-to-mild coronary calcification (CAC score < 100) as a referent, multivariable analysis showed that presence of obesity (OR 0.564; 95% CI 0.395, 0.806; P 0.002), body mass index (OR 0.945; 95% CI 0.920, 0.971; P < 0.001 ), body weight (OR 0.987; 95% CI 0.979, 0.995; P 0.001), and body surface area (OR 0.582; 95% CI 0.369, 0.920; P 0.020) were inversely associated with moderate-to-severe coronary calcification (CAC score ≥ 100). This study extends the concept of obesity paradox to symptomatic patients undergoing coronary artery calcium score assessment. However, biological explanation(s) of this paradox remains unanswered.